2012
DOI: 10.4103/1947-2714.93385
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced hepatotoxicity in a tertiary care hospital in Rural South India

Abstract: Background:Liver is the main organ for metabolism of drugs and hepatotoxicity is a potential adverse effect for most drugs.Aims:This study was to study the frequency of drug-induced hepatotoxicity and to find the common drugs causing hepatotoxicity.Materials and Methods:The study was conducted at a tertiary care hospital in rural India. It is a study based on case series analysis. All patients with an abnormal liver function report, between July 2006 and July 2007, were included in the studyResults:The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another study by Amer et al (2010) reported males (n=75, 59.5%) were more affected then females (n=51, 40.5%) [16,21]. Drug-induced hepatotoxicity was more common in males (n=36, 56%) than females (n=29, 44%) [22]. In this study, the incidence of anti-TB DIH is higher in male patients (n=146, 76.8%) than female patients (n=44, 23.2%).…”
Section: Discussionmentioning
confidence: 43%
“…Another study by Amer et al (2010) reported males (n=75, 59.5%) were more affected then females (n=51, 40.5%) [16,21]. Drug-induced hepatotoxicity was more common in males (n=36, 56%) than females (n=29, 44%) [22]. In this study, the incidence of anti-TB DIH is higher in male patients (n=146, 76.8%) than female patients (n=44, 23.2%).…”
Section: Discussionmentioning
confidence: 43%